Material selection for the gas containment system of a compressed natural gas carrier fleet. (February 2016) - Gaiotti, M.; Rizzo, C.M.; Rizzuto, E.; Vernengo, G.
Highlights: Different gas containment system materials for CNG ships are analyzed by FEM structural computations. A holistic design strategy is used to account for gas containment system scantling material on fleet performance. Both technical and economic performance are accounted for ranking the designed fleets. A multi-objective decision making environment is proposed to select the optimal CNG fleet configuration. Abstract: In this work, the possible exploitation of fiber-reinforced composites in the context of maritime transportation of compressed natural gas (CNG) is investigated. In addition to a more conventional steel configuration, two different fiber materials, carbon and glass, are considered as construction materials for pressure vessels (PVs) to be stored on board ships, with thickness optimized by FEM analysis. The considered scenario is represented by the transportation of CNG from an offshore well to a terminal on shore. Fleets of ships carrying CNG in pressure vessels manufactured with the investigated materials are generated by means of a ship synthesis model (SSM) software and compared on the basis of technical and economical indicators. The choice of the construction material influences considerably the weight of the PVs, which represent a major item of total ship weight and reflects directly on the general transport performances in terms of resistance, seakeeping and reliability in the service. On the other hand, capital as well as operating expenditures are considerably affected by the choice. When exploring the design space, the ship synthesis model is able, at a preliminary stage of the design, to account for the various technical and economical aspects, their implications and relationships. Results are presented of computations carried out in a specific case, identified by the annual gas production and other characteristics of the well terminal and a cruising route for the ships. The comparison is carried out on the basis of the cost per transported unit of gas and of the percentage of success in the transportation process. The computations show that the choice of the PV material has a key influence on the results in terms of optimal number, dimensions and speed of the ships.